2007
DOI: 10.1093/cercor/bhm134
|View full text |Cite
|
Sign up to set email alerts
|

A Common Neural Network for Cognitive Reserve in Verbal and Object Working Memory in Young but not Old

Abstract: Epidemiologic evidence suggests that cognitive reserve (CR) mitigates the effects of aging on cognitive function. The goal of this study was to see whether a common neural mechanism for CR could be demonstrated in brain imaging data acquired during the performance of 2 tasks with differing cognitive processing demands. Young and elder subjects were scanned with functional magnetic resonance imaging (fMRI) while performing a delayed item response task that used either letters (40 young, 18 old) or shapes (24 yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
104
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 40 publications
7
104
0
3
Order By: Relevance
“…Finally, in the field of cognitive reserve, it has been suggested that control processes may be a relevant component of reserve (see Stern et al, 2008). This is reliable with the idea that the anterior cingulate cortex integrates input from various sources and contributes to the regulation of processing in other brain regions (see Bush et al, 2000;Shackman et al, 2011).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Finally, in the field of cognitive reserve, it has been suggested that control processes may be a relevant component of reserve (see Stern et al, 2008). This is reliable with the idea that the anterior cingulate cortex integrates input from various sources and contributes to the regulation of processing in other brain regions (see Bush et al, 2000;Shackman et al, 2011).…”
Section: Discussionmentioning
confidence: 79%
“…For this purpose, two cognitive domains particularly relevant in aging and reserve studies were selected: memory (Buckner, 2004) and executive functions (Buckner, 2004;Siedlecki et al, 2009;Stern et al, 2008). Verbal episodic memory was assessed using the 16-word delayed recall from…”
mentioning
confidence: 99%
“…More precisely, Stern et al (2008) identified similar task-related activations associated with proxy measures of cognitive reserve across two tasks with distinct cognitive demands. They speculated that cognitive reserve may have a specific neural substrate, such that people with high level of cognitive reserve would be able to engage this network in the service of any task.…”
Section: Discussionmentioning
confidence: 86%
“…For a given task, high cognitive reserve would be associated with reduced cerebral activation (neural efficiency) in regions typically engaged in task performance, whereas increased activation in less typical regions would reflect neural compensation. Previous work demonstrated the diversity of the cerebral sites manifesting neural reserve and compensation, suggesting some task-related specificity (although the idea of a generic cognitive reserve network has been put forward (Stern, 2009;Stern et al, 2008), see Discussion). Moreover, cognitive reserve may impact on the interaction between brain regions, in a way comparable to the relationship between individual differences in processing speed and the efficiency of interactions between brain regions (Rypma et al, 2006)" (p. 8).…”
mentioning
confidence: 99%
“…Since then, this model has been replicated and extended [Zahodne et al, 2013]. Despite these findings, few researchers have explored the brain networks associated with CR using neuroimaging techniques [Stern et al, 2005, 2008] and, none have explored such properties when individuals are at rest (i.e., independently of a task‐performance).…”
Section: Introductionmentioning
confidence: 99%